Effect Of Ethanol Extract Of Kenikir (Cosmos caudatus Kunth.) Leaves in Blood Glucose, Cholesterol and Histopathology Pancreas of Male White Rats (Rattus norvegicus) - Tandi, Joni; Claresta, Jong A.; Ayu, Gusti; Irwan, Irwan (Indonesian Journal of Pharmaceutical Science and Technology, 2018)
The aim of this study was to investigate the effects extract of Kenikir in male rats parameters blood glucose, cholesterol and histopathological of the pancreas. Thirty rats were divided into six groups, and each group consists of five individuals with the details of groups I, II, and III as control groups and groups IV, V, and VI for the experiments. Group I: normal control was given NaCMC 0,5%; Group II: control negative was given Streptozotocin 30 mg/kgBW i.p, high feed fat 25 g/day, and the positive control was given met form in 45 mg/kgBW, and the experimental groups were each given extract of the kenikir leaves with dose 100 mg/kg BW, 200 mg/kgBW , and 400 mg/kg BW. The results showed that there were secondary metabolites contained in the extract of leaves of kenikir. Giving the extract of kenikir leaves at the dose of 200 mg/kg is effective in lowering the blood glucose levels, extract of leaves of kenikir with the dose of 400 mg/kg is effective to reduce the total cholesterol levels and regenerate pancreatic tissue, and extract of leaves of kenikir with the dose of 100 mg/kg BW did not give any maximum impacts to decrease the blood glucose. Keywords: Cholesterol, diabetic, histopathology, kenikir leaves ethanol extract